The Complexity of Job Competition between Humans and Robots in the Era of the Industrial Revolution 4.0 - Alven Qois Charisteas; Milati Auliyah; M.Sadam Al Jabbar; Ramadani Ramadani; Rizki Fadilah Ramadhan; Rama Wijaya Abdul Rozak (Syntax Corporation Indonesia, 2023)
The current era of the industrial revolution 4.0, has a very varied influence on various fields, one of which is the industrial sector, with the growing automation of machines and robots, coupled with intense job competition, every worker must prepare for the possibilities that will occur. in the future, humans must begin to be aware of the rapid development of current technology, and see several possibilities that will occur, later robots may affect human employment, starting from job competition, to jobs being taken over by robots, this is will cause anxiety for workers or actors in the industrial sector. Competition in the world of work today does not only involve humans but is a result of current technological developments, resulting in robots being involved and starting to enter the scope of human work competition. With the emergence of this phenomenon, humans are required to improve their skills and abilities to be able to keep up with the robots when there is competition later. The method used in this study included multiple linear regression methods with a sample of 50 informants using the formula Slovin’s study aims to find out whether these possibilities will occur in the future, and then whether there is an influence from robots and job competition on the future of workers. The results obtained from this study indicate that the influence of robots and job competition has a positive and significant impact on the future of workers and to compensate for robots so that they do not dominate human jobs, these workers should continue to improve their skills, knowledge, and skills.